Molecular Cloning of Monkey Histamine H4 Receptor - Tamaki Oda; Shun-ichiro Matsumoto; Mitsuyuki Matsumoto; Jun Takasaki; Masazumi Kamohara; Takatoshi Soga; Hideki Hiyama; Masato Kobori; Masao Katoh (Elsevier, 2005)
Histamine H4 receptor is considered as a novel therapeutic target for allergic diseases. To enhance the knowledge about species difference, which is essential for drug discovery research, monkey H4 receptor was identified. Monkey H4 receptor was characterized to have comparable similarity with its human counterpart. Discovery of monkey H4 receptor will contribute to a better interpretation of effective drug discovery. Keywords:: histamine, H4 receptor, G-protein coupled receptor